The Diagnosis and Therapy of Degenerative Knee Joint Disease: Expert Consensus from the Chinese Pain Medicine Panel - Dong Huang; Yan-Qing Liu; Li-Shuang Liang; Xue-Wu Lin; Tao Song; Zhi-Gang Zhuang; Suo-Liang Wang; Hong-Guang Bao; Lin Wang; Xian-Wei Zhang; Zhi-Gang Cheng; Bao-Lin Duan; et al. (Pain Research and Management)
At present, there are many constantly updated guidelines and consensuses on the diagnosis and treatment of osteoarthritis both at home and abroad. The recommendations established using methods of evidence-based medicine has experienced strict research on controlling bias and promoting reproduction rate. As a result, the previous evidence was reevaluated, and a lot of changes were provoked in the diagnosis and treatment concept of osteoarthritis. However, several methods not recommended by foreign guidelines are still in use in the current clinical practice in China. On the one hand, Chinese experts have not reached extensive consensus on whether it is necessary to make changes according to foreign guidelines. On the other hand, almost all the current relevant guidelines are on osteoarthritis, but the lesions around knee joints which, as a whole, bear the largest weight in human body, cannot be ignored. For this purpose, Chinese Association for the Study of Pain (CASP) organized some leading experts to formulate this Chinese Pain Specialist Consensus on the diagnosis and treatment of degenerative knee osteoarthritis (DKOA) in combination with the guidelines in foreign countries and the expert experience of clinical practice in China. The consensus, which includes the definition, pathophysiology, epidemiology, clinical manifestation, diagnostic criteria, and treatments of DKOA, is intended to be used by first-line doctors, including pain physicians to manage patients with DKOA.